Human interface and the management of information : Interacting with information : Thematic area, HIMI 2020, held as part of the 22nd International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings.: Interacting with information : Thematic area, HIMI 2020, held as part of the 22nd International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings. Part II (2020) - Unknown
No abstract available